Антология выдающихся достижений в науке и технике. Часть 32: Альтернативная энергетика: состояние и перспективы развития - Баранов, Михаил Иванович (НТУ "ХПИ", 2016)
Приведен краткий научно-аналитический обзор о состоянии и перспективах мирового развития альтернативной энергетики, включающей ветроэнергетику, солнечную энергетику, геотермальную энергетику, биогазовую энергетику, приливную гидроэнергетику, водородную энергетику и малую гидроэнергетику.

Purpose. Implementation of brief analytical review of the state and prospect of development in the modern world of alternative energy, including wind energy, sun energy, geothermal energy, biogas energy, flood-tide water energy, hydrogen energy and small water energy. Methodology. Scientific methods of collection, analysis and analytical treatment of scientific and technical information in area of the present state of world energy and ways of its further development. Results. A brief scientific and technical review is resulted about the state and prospects of world development of basic types of alternative energy. It is shown that, in spite of comparatively small stake (to 10 %) of this untraditional energy in general world balance of making of electric power, world association taking into account the necessary changing in the nearest 50 years of present oil-gas «foundation» of energy on other with large raw material, potential and ecological possibilities are forced to invest large financial means in development of the indicated directions of alternative energy. Originality. First on the basis of materials of separate magazine publications, scientific monographs and internet-reports on power problem the brief analytical review of the state and prospects of world development of basic types of alternative energy is executed. Practical value. Deepening and spread of the scientific and technical learnings in area of functioning and ways of development of modern energy. Scientific popularization of arising up before society claimed tasks from global and important for all of humanity of power problem.
An anthology of the distinguished achievements in science and technique. Part 32: Alternative energy: state and prospects of development
Keywords: экономическая сила страны; возобновляемые источники энергии; ветроэнергетика; солнечная энергетика; гелиоэлектростанции мира; alternative energy; state and prospects of world development; review